Recent insights into the molecular mechanisms of simultaneous fatty acid oxidation and synthesis in brown adipocytes - Chang, Ji Suk (Frontiers in Endocrinology, 2023)
Brown adipocytes is a specialized fat cell that dissipates nutrient-derived chemical energy in the form of heat, instead of ATP synthesis. This unique feature provides a marked capacity for brown adipocyte mitochondria to oxidize substrates independent of ADP availability. Upon cold exposure, brown adipocytes preferentially oxidize free fatty acids (FFA) liberated from triacylglycerol (TAG) in lipid droplets to support thermogenesis. In addition, brown adipocytes take up large amounts of circulating glucose, concurrently increasing glycolysis and de novo FA synthesis from glucose. Given that FA oxidation and glucose-derived FA synthesis are two antagonistic mitochondrial processes in the same cell, it has long been questioned how brown adipocytes run FA oxidation and FA synthesis simultaneously. In this review, I summarize mechanisms regulating mitochondrial substrate selection and describe recent findings of two distinct populations of brown adipocyte mitochondria with different substrate preferences. I further discuss how these mechanisms may permit a concurrent increase in glycolysis, FA synthesis, and FA oxidation in brown adipocytes.